Features and prospects of resolving the political crisis in Venezuela - Mansurov, Timur Zufarovich; Rafailevna, Efimova Sabina (Linguistics and Culture Review, 2021)
The purpose of the research is to identify opportunities and prospects for resolving the political crisis in Venezuela proceeding from the current situation in the country. The specifics of the crisis processes in the socio-economic and political spheres, as well as the causes contributing to their deepening are considered. The authors analyze the conflict between the ruling regime and the opposition and the factors impeding the implementation of the political and economic measures pursued by the government to remove the country from the crisis. The authors research the actions performed by the authorities of the Chavist regime in promoting dialogue and seeking compromise both with the political opposition and other immediate parties to the conflict, including secret negotiations, and with the help of mediators. Particular attention is paid to the scenarios of crisis resolution in Venezuela developed by the author of the paper, named "negative", "positive", and "neutral". Each of the scenarios traces the actions of the main opposing forces, their capabilities to resolve the conflict in one or another direction, the involvement of regional and major world states and the possibilities of their implementation to date.